Pengaruh Soft Skill, Hard Skill dan Self-Efficacy terhadap Kesiapan Kerja Lembaga Pelatihan Kerja Seikou Gakkou Kabupaten Boyolali - Lia Hamidah; Alean Kistiani Hegy Suryana; Hari Purwanto (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
This study aims to explore the impact of soft skills, hard skills, and self-efficacy. It employs a quantitative research design involving 120 participants, with a sample size of 93. The findings indicate that the first variable (soft skills) does not have a significant impact on work readiness (Sig. = 0.060 > 0.05). Conversely, hard skills show a significant effect on the dependent variable (Sig. = 0.026 < 0.05), and self-efficacy also contributes significantly (Sig. = 0.000 < 0.05). Collectively, soft skills, hard skills, and self-efficacy demonstrate a significant influence on work readiness, with a calculated F-value of 53.812 and a significance level of 0.000 (< 0.05).